Challenges of living with an implantable cardioverter-defibrillator: A qualitative content analysis - Yaser Moradi; Farzin Mollazadeh; Hossein Jafarizadeh; Hossein Habibzadeh; Rahim Baghaei; Yousef Mohammadpour; Parivash Karimi (Kashan University of Medical Sciences, 2022)
Background: Living with an implantable cardioverter-defibrillator (ICD) in the body can be challenging for patients. Identifying these challenges is, therefore, crucial for health promotion. Objectives: This study was conducted to explore the challenges experienced by patients living with an ICD. Methods: A qualitative content analysis study was conducted on 24 patients with an ICD. Purposive sampling and individual semi-structured interviews were conducted to collect the study data. After transcribing the interviews, content analysis was performed to analyze the data. Results: The participants were aged 35-60 years. Their education level varied between primary and tertiary levels. The participants had an ICD for an average of 35.70 ± 11.36 months. Three themes emerged, including "feeling disabled," "problematic adaptation," and "Financial constraints." These themes indicated the most important challenges experienced by the participants. Conclusion: Patients with an ICD suffer more from psychological and financial problems than physical problems. Nurses and other health-care workers play a key role in supporting these patients.